2007
DOI: 10.5009/gnl.2007.1.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Hepatitis-B-virus-associated Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent and malignant diseases worldwide. Epidemiological studies have clearly demonstrated that chronic hepatitis B virus (HBV) infection is a major etiological factor in the development of HCC. The pathogenesis of HBV-associated HCC has been studied extensively, and the molecular changes associated with malignant transformation have been identified. The predominant carcinogenic mechanisms of HBV-associated HCC are chronic inflammation and the effects of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…Approximately 600,000 humans die every year due to liver cancer that develops from hepatitis B virus (HBV) infection (Franco et al 2012). Chronic HBV infection induces persistent hepatocyte inflammation, oxidative DNA damage, uncontrolled cellular proliferation, fibrosis and cirrhosis, which eventually culminates in hepatocellular carcinoma (Park et al 2007). Since steatosis and inflammation are two important mechanisms that mediate HBV-dependent hepatocellular carcinoma, and ligand activation of PPARβ/δ prevents hepatic steatosis and inflammation, the present study examined the hypothesis that ligand activation of PPARβ/δ inhibits liver cancer in HBV transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 600,000 humans die every year due to liver cancer that develops from hepatitis B virus (HBV) infection (Franco et al 2012). Chronic HBV infection induces persistent hepatocyte inflammation, oxidative DNA damage, uncontrolled cellular proliferation, fibrosis and cirrhosis, which eventually culminates in hepatocellular carcinoma (Park et al 2007). Since steatosis and inflammation are two important mechanisms that mediate HBV-dependent hepatocellular carcinoma, and ligand activation of PPARβ/δ prevents hepatic steatosis and inflammation, the present study examined the hypothesis that ligand activation of PPARβ/δ inhibits liver cancer in HBV transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of MTA1 overexpression is much higher in HBV-associated HCC (HBV–HCC) than in HCV-associated HCC [11]; however, the mechanisms underlying this observation remain elusive. The direct effects of HBV and indirect effects of inflammation, regeneration, and cirrhosis contribute to the development of HBV–HCC [15, 16]. Few studies have reported the potential role of MTA1 in HBV-associated hepatocarcinogenesis [1719].…”
Section: Introductionmentioning
confidence: 99%
“…After inflammation, consistent necrosis of hepatocytes accompanied by rapid regeneration may lead to the accumulation of mutations and the selection of cells with malignant phenotypes. 20,21 That is, persistent inflammation in the remaining liver provides "field-effects" to develop second primary HCCs after hepatectomy. Intrahepatic HBV-DNA, especially at high titer, may also cause active inflammation in the remaining liver parenchyma, contributing to a change in tumor microenvironment, increasing HCC recurrence after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Alternatively, HBV itself may activate oncogenic signaling pathways, either cis-activation through integration of viral genetic material into host cellular DNA or trans-activation by viral products such as HBx protein. 21 FIGURE 1. Cumulative tumor recurrence in relation to intrahepatic hepatitis B virus (HBV)-DNA titers in nontumor liver tissue surrounding hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 99%